Experimental Analysis of Low-Energy Impact Damage in Composite Material Airfoils - Ilse Jauregui Bogarin; Virginia G. Angel; Miriam Siqueiros Hernández; Emmanuel Santiago Durazo Romero; Hernán D. Magaña-Almaguer; Lidia Esther Vargas Osuna; Benjamín González Vizcarra (Fibers)
The use of composite materials in aerospace structures has led to significant weight reductions and improved performance. However, their behavior under low-energy impact remains a critical concern due to the potential initiation of barely visible damage. This study investigates the crack initiation mechanisms in composite airfoil profiles subjected to low-energy impact, simulating real-world scenarios such as hail or bird strikes. Two types of airfoil profiles were fabricated using bidirectional carbon fiber reinforced polymer (CFRP) with epoxy resin and tested under ASTM D7136 impact conditions. Tensile tests following ASTM D3039 were conducted to assess post-impact mechanical behavior. The damage patterns were analyzed using high-resolution microscopy and non-destructive inspection techniques. Results revealed that damage severity and propagation depend on impact energy levels and airfoil geometry, with SC(2)-0714 exhibiting better impact resistance than GOE777-IL. Microscopic analysis confirmed that delamination initiated at 45° fiber orientations, expanding along interlaminar regions, while airfoil curvature influenced the impact energy dissipation.